Role of Seaweeds for Improving Soil Fertility and Crop Development to Address Global Food Insecurity - Ali Rafi Yasmeen; Theivanayagam Maharajan; Ramakrishnan Rameshkumar; Subbiah Sindhamani; Balan Banumathi; Mayakrishnan Prabakaran; Sundararajan Atchaya; Periyasamy Rathinapriya (Crops, 2025)
Seaweeds and their derived products have long been valued in organic agriculture, serving roles in biofertilizers, biostimulants, and soil conditioners due to their rich content of bioactive compounds. With increasing concerns over the negative impacts of synthetic agrochemicals on food security and environmental health, seaweeds offer a sustainable alternative for improving soil fertility and crop productivity. This review synthesizes recent findings on the use of seaweeds to enhance soil physicochemical properties, stimulate beneficial microbial activity, and improve nutrient availability. Furthermore, it highlights how seaweed applications can mitigate various abiotic stresses, such as droughts, salinity, and nutrient deficiency, by enhancing antioxidant defenses and promoting physiological and biochemical resilience in plants. Key agronomic benefits include improved seed germination, root development, photosynthesis, biomass accumulation, and yield performance. By acting as natural soil amendments, seaweeds support sustainable soil management and contribute to long-term agricultural resilience. This review emphasizes the urgent need for standardized application strategies and integrated research to unlock the full potential of seaweed-based solutions in sustainable farming systems.